Biotechnology and Plant Disease Management - Punja, Z.K (CABI, 2014)
Plants must continuously defend themselves against attack from fungi, bacteria, viruses, invertebrates and even other plants. The regulation mechanisms of any plant–pathogen interaction are complex and dynamic. The application of biochemical and molecular genetic techniques has resulted in major advances in elucidating the mechanisms that regulate gene expression and in identifying components of many signal transduction pathways in diverse physiological systems. Advances in genomics and proteomics have profoundly altered the ways in which we select and approach research questions and have offered opportunities to view signal transduction events in a more systemic way. Although many disease resistant genes and signalling mechanisms are now characterized, it is still ambiguous whether and how they can be engineered to enhance disease resistance. Caution is needed when assessing manipulation strategies so that the manipulations will achieve the desired results without having detrimental effects on plant growth and development. This chapter discusses some other effective approaches for identification of signal transduction components, such as RNA interference (RNAi), yeast two-hybrid system and proteomics approaches